KARAKTERISTIK FISIKOKIMIA DAN SENSORI MIE UBI KAYU DENGAN SUPLEMENTASI ISOLAT PROTEIN KEDELAI - Retno Setyawati; Hidayah Dwiyanti; A.R. Siswanto B.W. (Faculty of Agricultural Technology, University of Jember, 2011)
The aims of this research were: (1) to find the appropriate of suplementation of isolated soybean protein to produce cassava noodle with high protein content, high extensibility, low cooking loss, and elastic texture; and (2) to find of the blanching period to produce cassava noodle with high extensibility, low cooking loss, and elastic texture. The experimental design used was Randomized Block Design (RBD). The factor tried were suplementation of isolated soybean protein (5, 10, and 15 %), and period of blanching (5; 7,5; and 10 minute). Each combinations of treatment were repeated three times, so there were 27 experimental units. Variables observed were chemical, physical and sensory properties. The result showed that 15% suplementation of isolated soybean protein and 10 minute period of blanching was produce cassava noodle with rather elastic texture (scale of 2.27), yellowish colour (scale of 3.20), rather beany flavor (scale of 2.47), rather delicious flavor (scale of 2.33), and preference was like (scale of 2.60). The chemical composition of product were 11.74 % (wb) of water content, 1.45 % (db) of dissolved protein content, 3.49 % (db) of ash content, 10.35 % (db) of fiber content, 9.71 % (db) of total protein content, 1.73 % (db) of fat content, and 73.33 % (db) of carbohydrate by difference content. Physical properties of this product were 20.9 % extensibility and 4.73 % (db) of cooking loss. Keywords: cassava noodle, isolated soybean protein, physical properties, sensory propertie